AN ANALYTICAL STUDY OF THE REALITY OF SPORTS HOOLIGANISM IN SPORTS STADIUMS FROM THE POINT OF VIEW OF STUDENTS OF THE COLLEGE OF PHYSICAL EDUCATION AND SPORTS SCIENCES AT ANBAR UNIVERSITY - Yaseen Ali Khalaf; Ziyad Mishaal Farhan (Proximus Journal Publishing, 2024)
The research aimed to identify the reality of sports hooliganism in sports stadiums from the point of view of students of the College of Physical Education and Sports Sciences at the University of Anbar, as the researchers used the descriptive approach in the survey method for its suitability and the nature of the research problem, and the research community included students of the College of Physical Education and Sports Sciences at Anbar University for the morning study for the academic year (2024-2025), which numbered (329) male and female students, the study sample was randomly selected and numbered (180) students with a percentage of (54.71%) from the total research community, and the results of Research and for all areas studied on low evaluation scores, and contribute to all areas of research studied to raise sports hooliganism in sports competitions, and the researchers recommended the need to work on the application of the law and strictly against all individuals violators, and to establish educational programs and courses due to their importance in spreading sports culture among the masses, and keep sports media away from news that provokes hooliganism through audio and read channels
Keywords: hooliganism; sports fields; students